The experience of the home context among family members and health professionals - Silvia Yuri Sugiura; Nayla Tamara de Godoi Caceres; Maria Ribeiro Lacerda; Luana Tonin; Jessica Alline Pereira Rodrigues; Jaqueline Dias do Nascimento (Universidade Federal de Santa Maria, 2018)
Aim: to understand the experience of the home context in the perspective of family caregivers and health professionals and to present a theoretical model that represents this experience. Methods: the Data-Based Theory was developed in a Home Care Service. Data were collected from February to December 2016 using a semi-structured in-depth interview with 22 participants, who were divided into two sample groups. Results were analyzed according to the constant comparative method, revealing the significant theoretical coding. Results: the understanding of this phenomenon occurred through the following categories: Entering Home Care (cause); Interacting with the social support network (strategy); Expressing perceptions of one's experience of care (intervening condition); and Experiencing home context aspects (consequence). Final considerations: the participants' experience revealed that home care has its own context, including a cause, strategy, intervening condition and consequence, which must be taken into consideration by those involved with this type of care.